Detection and Endodontic Treatment of Unusual Anatomic Variations in Second Premolars: A Case Report - Davaji, Mina; Valizadeh, Mahsa; Karimpour, Sahar (Iranian Endodontic Journal, 2023)
Endodontic treatment of second premolars is challenging due to their complex anatomy and the likelihood of anatomical variations. The current report presents successful treatments of mandibular and maxillary second premolars with different anatomies in a single patient. The first case involved a patient referred from a general practitioner who was unable to complete the root canal treatment of her mandibular second premolar with four root canals. The initial radiograph showed an apical radiolucency, periodontal ligament (PDL) widening, and a fast break suggesting the possibility of root canal branching. With the diagnosis of previous treatment and chronic apical periodontitis, the tooth was successfully retreated with the aid of cone-beam computed tomography (CBCT), a dental operating microscope, and ultrasonic tips. The second case was a maxillary second premolar with Vertucci’s type VI root canal morphology, which was not responsive to pulpo-periapical tests. Along with a deep carious lesion and a PDL widening on the initial radiograph, a diagnosis of necrosis with chronic apical periodontitis was made. The root canals were located and treated using a combination of radiography with different angulation and CBCT. Both teeth were clinically and radiographically asymptomatic at the 4-month follow-up session. This case report highlights the importance of thorough preoperative evaluation and the use of advanced technology and techniques in achieving successful endodontic treatment outcomes.